Analisis Asuhan Keperawatan Pasien dengan Myasthenia Gravis pada Kehamilan - Ranukusuma, Candradewi Mahardika; Kariasa, I Made (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze cases of myasthenia gravis (MG) in pregnancy using the Roy Adaptation model approach. The research method used a case study approach with a case of a patient experiencing MG-weighted flaccid tetraparesis during pregnancy. The research results showed that the nursing care plan used the Roy adaptation model. The main needs found are nutrition (swallowing disorders), mobility (impaired physical mobility), sensation (acute pain) and protection (risk of infection). Interventions provided include self-care assistance: eating, exercise promotion: muscle strength, pain management and infection control. In conclusion, Roy's adaptation model approach is useful in this case because it focuses on the patient's ability to adapt to his illness. The patient had a disease that had been going on for years and had worsened due to her pregnancy. Providing appropriate nursing care can speed up patient recovery so that the length of stay is shorter. Keywords: Roy Adaptation, Nursing Care, Myasthenia Gravis